2017
DOI: 10.1101/234559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supergene evolution triggered by the introgression of a chromosomal inversion

Abstract: Supergenes are groups of tightly linked loci whose variation is inherited as a single Mendelian locus and are a common genetic architecture for complex traits under balancing selection 1 . Supergene alleles are long-range haplotypes with numerous mutations underlying distinct adaptive strategies, often maintained in linkage disequilibrium through the suppression of recombination by chromosomal rearrangements [2][3][4][5] . However, the mechanism governing the formation of supergenes is not well understood, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 48 publications
4
74
0
3
Order By: Relevance
“…Each year, new systems with tightly linked clusters of genes are discovered, pointing to the importance of supergenes in the evolution of certain classes of complex traits, including mimetic coloration in butterflies, self-incompatibility in plants, mating strategies in birds, mating types in fungus, and social organization in ants [1,2,[7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each year, new systems with tightly linked clusters of genes are discovered, pointing to the importance of supergenes in the evolution of certain classes of complex traits, including mimetic coloration in butterflies, self-incompatibility in plants, mating strategies in birds, mating types in fungus, and social organization in ants [1,2,[7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…As in the Formica supergene, the 'modules' often span very small portions of the genome and exhibit a different evolutionary history from one another and from whole genome patterns. Jay et al [10] demonstrate that these alternative topologies result in some cases from introgression of modules between species. The contribution of introgression to evolutionary patterns in the Formica supergene remains to be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…While this may indicate introgression from the parental lineage that is least represented in the genomic background of intermediate populations, in our case such asymmetry may also result from a lower power to detect introgression from the dominant parental background. Whether some of those SNPs result from adaptive introgression, as has been revealed in Heliconius butterflies (Heliconius Genome Consortium, 2012; Jay et al, 2018), warrants further study.…”
Section: Discussionmentioning
confidence: 95%
“…Over time, drift and selection can lead to the emergence of barriers to gene flow that increase reproductive isolation, resulting in heterogeneous patterns of differentiation and introgression across the genome (Barton & Bengtsson, 1986; Ravinet et al, 2017; Safran & Nosil, 2012). Genomic regions with low rates of introgression are more likely to be associated with divergent selection and reproductive isolation (Gompert & Buerkle, 2009; Heliconius Genome Consortium, 2012; Jay et al, 2018; Mallet, 2005; Mallet & Barton, 1989). Assessing the genetic structure of hybrid zones can therefore shed light on the evolutionary processes at play during the early stages of speciation by revealing the number and distribution of loci presenting deviant patterns of differentiation and introgression compared to the genome‐wide average (Bierne, Welch, Loire, Bonhomme, & David, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One important insight of both within‐ and between‐species genome comparisons has been that interspecific hybridizations and genome duplication are rather common; the per‐generation frequency of changes in ploidy after hybridization seems to be on the same order of magnitude as that of point mutations (Ramsey and Schemske, , ). While adaptation often relies on new mutations or new combinations of existing variants, large genomic rearrangements provide radically novel routes of adaptation (Martin and Jiggins, ), as observed in butterflies and mosquitoes (Heliconius Genome Consortium, ; Fontaine et al , ; Jay et al , ). The systematic analysis of plant genomes has shown that this also applies to them (Rieseberg, ; Wissemann, ; Arnold et al , ; Suarez‐Gonzalez et al , ), especially after crosses between taxa that are not even in the same genus (Joly et al , ).…”
Section: Learning From Plant Genomesmentioning
confidence: 99%